Nurturing short-term rentals in Thailand - Leelawath, Watcharas; Roth, Anita; Chuenchomlada, Bussaracum; Schipani, Steven (ADB Briefs)
This brief analyzes the importance of Thailand’s short-term rentals (STRs) to tourism and shows why measures to ensure providers are fully regulated would improve quality assurance, increase public revenues, and help entrepreneurs access financing.